2013
DOI: 10.1007/s12639-013-0399-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of Setaria worms collected from cattle

Abstract: Morphological characters of Setaria sp. collected from cattle and buffaloes were studied. Three species Setaria digitata, Setaria cervi and Setaria labiatopapillosa were identified in the present study. Out of the 500 cattle screened 187 were found to harbour worms. 56.8 % (106) of animals with S. digitata, 24.13 % (45) had S. cervi and 18.96 % (36) had S. labiatopapillosa. Morphological characters of male and female worms of all the three species were studied in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 10 publications
0
20
2
Order By: Relevance
“…Setaria labiatopapillosa ( syns., Setaria cervi ) (Figure-4) prevalence in Aceh cattle slaughtered in a Banda Aceh slaughterhouse is 4%. This result is much lower compared to research carried out Bino and D’Souza [21] which found that out of the 500 cattle screened, 187 (37.4%) were found harboring Setaria worms in the peritoneal cavity. Three species of Setaria, namely, Setaria digitata, S. cervi, and S. labiatopapillosa were observed in the Bino study.…”
Section: Resultscontrasting
confidence: 60%
“…Setaria labiatopapillosa ( syns., Setaria cervi ) (Figure-4) prevalence in Aceh cattle slaughtered in a Banda Aceh slaughterhouse is 4%. This result is much lower compared to research carried out Bino and D’Souza [21] which found that out of the 500 cattle screened, 187 (37.4%) were found harboring Setaria worms in the peritoneal cavity. Three species of Setaria, namely, Setaria digitata, S. cervi, and S. labiatopapillosa were observed in the Bino study.…”
Section: Resultscontrasting
confidence: 60%
“…Although S. cervi became a model species for anti-filarial drugs and treatment methods decades ago (Singhal et al ., 1969), not much is known about its presence in the wild. Known definitive hosts of S. cervi are: the moose ( Alces alces ), the red deer ( Cervus elaphus ), the sika deer ( Cervus nippon ), the Asian wapiti ( Cervus elaphus sibirica ), the muntjac ( Cervus muntjac) , the chital ( Axis axis ), the fallow deer ( Dama dama ) (Yeh, 1959; Wang et al ., 1990; Anderson, 2000) but also cattle; Bos taurus (Baqui and Ansari, 1976; Sundar and D'Souza, 2015) and Bubalus bubalus (Almeida et al ., 1991). Infection with S. cervi can lead to pathological changes in the central nervous system in definitive hosts (Blažek and Dykova, 1968; Wang et al ., 1990).…”
Section: Introductionmentioning
confidence: 99%
“…), mosquitotransmitted nematodes (e.g., Setaria sp. [42,43]), as well as two recently discovered Anopheles aviviruses (e.g., Anopheles avivirus variant 1 and variant 2) [44] ( Table 2). The details of all parasite sequences ampli ed and their taxonomic information for each mosquito are provided in Additional le 8: Table S6.…”
Section: Identi Cation Of Eukaryotic Parasites and Viruses From Indivmentioning
confidence: 99%